Canada's Assisted Human Reproduction Act: Pragmatic Reforms in Support of Research - Bubela, Tania; Kleiderman, Erika; Master, Zubin; Ogbogu, Ubaka; Ravitsky, Vardit; Zarzeczny, Amy; Knoppers, Bartha Maria (Frontiers in Medicine, 2019)
Canada’s Assisted Human Reproduction Act is long overdue for Parliamentary review. We argue that the current regulation of research using human reproductive materials is not proportionate, not responsive to the uncertain threats posed to human and environmental health and safety, and is not considerate of diverse values in a democratic society. We propose tailored regulatory carve-outs for in vitro research for currently prohibited activities, such as gene editing, and for the exercise of Ministerial Discretion for access by Canadians to experimental in vivo interventions that are currently prohibited, such as mitochondrial replacement therapy. Our recommendations are bounded by constitutional constraints that recognize political and practical challenges in keeping oversight of this research under Federal jurisdiction, whether conducted in academic or private sectors. The proposed nuanced regulatory scheme should be overseen by a new national Agency, modeled on a blend of the Canadian Stem Cell Oversight Committee and Assisted Human Reproduction Canada.